Physicochemical and sensory assessment of partial corn substitutions with carotenoid-containing non-traditional flours during tortilla preparation - Artavia González, Graciela (2022)
Tortilla is a staple food for several countries and a gluten-free alternative and can be enriched using other non-traditional flours to improve their nutritional value. Three different lime and moisture concentrations were tested, and 0.25 and 56.34 g/100 g were selected as the best parameters to formulate during the rest of the survey. Once these conditions were determined, three different flours of sweet potato, peach palm, and cassava, at levels of 10 and 25 g/100 g, were partially used to substitute nixtamalized corn during the tortilla preparation. Several nutritional parameters of the flours were determined, including amino acid, mineral, fatty acid, sugar profiling as well as dietary fiber (sweet potato ≈ corn > cassava > peach palm), and carotenoids (peach palm > sweet potato > cassava ≈ corn). Moisture behavior and capacity of rollability during tortillas storage were also monitored for 15 days at 4 °C. Of all substitutions, only with sweet potato substitutions and the cassava substitution at a 10 g/100 g level, the typical puffing for a traditional tortilla is observed. Meanwhile, substitutions using peach palm and cassava flour showed the most degradation in storage. Sweet potato and peach palm (60.0 and 58.8 g/100 g) are less starchy ingredients than corn and cassava (87.8 and 85.30 g/100 g). Also, resistant starch for the tortillas ranged from 0.945 to 1.336 (cassava > peach palm > sweet potato), values higher than those found in a corn tortilla. Sensory analysis was also performed; both sweet potato and peach palm substitutions at 25 g/100 g obtained the lowest values of approval, by a consumer panel, for color and taste, respectively. Rollability was diminished as refrigeration time progressed, but sweet potato tortilla seems to withstand degradation (4.67–5.00 rollability scale) more so than the control or other treatments (i.e., < 4). Overall, the partial substitution of corn flour improved the resistance to shear and deformation; this was especially true for the sweet potato substitution at day 0. Sweet potato substitutions generated a tortilla with a significantly higher induction period (ca. 45 hours, p < 0.05) and calculated shelf life (ca. 5 hours) than the other treatments. It can be demonstrated that using non-traditional flours can improve several tortilla parameters and be an additional vehicle for carotenoids in the diet.